Exploring moral values of the main character in “Dead Poets Society” - Qaniu, Fitrahmel Razaq; Sarair, Sarair; Netta, Ayuna (ACCENTIA: Journal of English Language and Education, 2024)
This study conducted a qualitative analysis of the moral values depicted by the main character in the movie "Dead Poets Society." The film centers around students in an all-boys preparatory school, guided by an inspirational English teacher. The study explored the moral values demonstrated by the main character and their impact on the perceptions and actions. The data comprised the main character’s dialogues and actions, as presented in the film, while considering the film's social and cultural context. Ethical and moral philosophy approaches were employed to identify and assess the exhibited moral values. The findings unveiled several key moral values embodied by the main character. Firstly, the main character's rebellion against societal norms displays the importance of freedom of thought and self-expression. Secondly, the character's display of courage emphasizes the value of standing up to pressures and following one's conscience. Thirdly, the significance of friendship and solidarity in confronting life's challenges is evident in the narrative. Lastly, the film underscores the importance of embracing uniqueness and individuality in the journey of self-identity. This study provides profound insights into the moral values depicted by the main character, serving as a valuable basis for discussions and reflections within the realms of moral education and personal development. Moreover, the study contributes to a deeper understanding of the far-reaching influence of moral values in shaping individuals' lives within society's fabric.